Design, molecular docking, and DFT analysis of dioxoisoindoline derivatives as potential anticonvulsant agents targeting epilepsy-associated proteins - Safi Ali, Reem; Oday Ezzat, Mohammed (Pharmakeftiki, 2025)
This study attempts to address the necessity of developing substitute therapies for antiepileptic medications. It suggests utilizing molecular docking and dioxoisoindoline derivatives in a theoretical chemical investigation to identify possible substitute medications that could be used in the treatment of epilepsy. In this study five compounds show different activities against particular proteins related to epilepsy treatment; especially compound R3 shows high negative values when it is associated with the three studied proteins. A density functional theory (DFT) approach was employed in order to identify the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) for the five herein studied compounds; it was also used in order to calculate the gap between HOMO and LUMO, the ionization potential, the electron affinity, the electronegativity, as well as the softness and hardness of the molecules, among other chemical characteristics. Overall, this study highlights the need of developing efficient epilepsy treatments and provides a preliminary analysis of possible drugs.